Processamento fonológico em adultos alfabetizandos com quadro de deficiência intelectual - Severino, Camila de Lima (2020)
This research is an exploratory study based on psychometric assessment and observational method on the phonological processing of adults diagnosed with intellectual disability (ID) in literacy process. Considering this scientific object of few bibliographic references - adults literacy with atypical learning – a cooperative investigation between Psycholinguistic and Phonology was constructed, in order to study the extent to which limitations in phonological capacity interfered in the development of reading and writing in these people. As theoretical subsidy of the relations between cognition, language and typical and / or atypical learning, it was used the contributions of Morais (1996), Ehri (2005), Maia (2008; org., 2015), Dehaene (2012; 2013), Scliar-Cabral (2012; 2015), Nicolielo and Hage (2011; 2014), Duarte and Velloso (2017), and others. As for the interface with the application of phonology contents, Cielo e Poersch (1998), Lamprecht (2004), Lemle (2007) and others served as basis. Methodologically, the investigation included five participants, two components from the main group (adult in literacy process + ID) and three from the secondary group (adult literate + ID). The data collection was structured by (a) five psychometric tasks (phonemic verbal fluency, rhyme and initial phoneme intruder, reading tests, dictation and grammatical judgment) and; (b) spontaneous material, from the school performance of the participants during classes; properly adequate to characterize the phonological processing itself and its effect on learning to read and write. With this apparatus, it was sought to support the hypothesis that the learning difficulties of reading and writing in the main group were fundamentally due to limitations in phonological processing; however, the result of the analyzes led to the reformulation of the hypothesis, which began to attest to the historic precariousness of metalinguistic stimuli and feedback from negative linguistic models, consequence of the lack of early cognitive intervention, as fundamental causes of limitations. Through the proposed research, it was expected to contribute to studies on phonological development and language cognition, especially in cases of cognitive impairment, and for those who are dedicated to the formulation of learning diagnoses in cases of atypical development. It was also sought to insert the adult with mental disorder in literacy process in scientific topics.